Correction: Comprehensive techno-environmental evaluation of an isolated PV/wind/biomass hybrid microgrid employing various battery technologies: A comparative analysis. - PLOS One Staff (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0317757.].